Análisis , diseño e implementación de un plan de gestión de seguridad de la información basados en la norma ISO/IEC 27001 para la Cooperativa de Ahorro y Crédito Nuevos Horizontes. - Gallegos Montero, Juan Abel (2015)
The credit union New Horizons city of Machala, presented several problems related to the area of ​​information security such as lack of controls and procedures for data security and support teams. Empirically it was to solve the deficiencies that were presented in the organization but in turn were exposed processes and information assets to a series of threats and vulnerabilities. With the above comes the need to analyze, design and implement a Plan Management Information Security using ISO 27001 and continuous improvement methodology PDCA (Plan, Do, Check and Act). With the completion of this project it was achieved titration mitigate risks of loss, theft or corruption of information; a guidance document good practice for the benefit of the entire organization for processes, users and customers of the bank was also established. For the development of the management plan ISO 27001 was used, the reason why this standard was chosen is because it allows us to define the requirements for establishing, implementing, maintaining and improving a management plan, whereby the achievement the objectives it seeks to ensure information security in the company; focused so that through the establishment of controls, mechanisms and procedures based on the ISO standard processes and ensure that information is being protected and managed effectively within the organization. Therefore, with the development of this Management Plan Information Security, it has managed to establish security policies based and based on the needs of the cooperative, providing a safe work environment and benefits to the entity.